Pedagogical values in educational theatrical texts By Taha Salem (Al-Academy, 2025)
The theatrical texts are distinguished by their clear intellectual contents of educational values ​​and artistic visions in the educational play, and that the educational play is not limited only to the present, but rather it works to review and document history and heritage, and present it in a way that makes it appropriate and interesting for new generations, and because it plays an important role in Transferring values ​​and knowledge and enhancing cultural communication between the past, present and future, which is an effective way to educate the public in an interactive and fun way.Including the search for four specific chapters for the researcher in the first chapter to the research problem that lies in answering the next question: (What are the educational values ​​in the texts and thus the educational ones by the author (Taha Salem)?Regarding the second chapter, which includes two sections, the first section is educational values ​​and the second section is educational theatre. He devoted three objectives to the research, defining the research, defining its procedures, and specifically the research community (Ain Qasdiyah), one text. In the fourth chapter, he built a study on the successes of some estates, then added a set of recommendations accompanied by the proposed properties that he found to complement his research.